Pengembangan Sistem Perencanaan Manajemen Risiko Bencana Di Indonesia - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
Indonesia is facing the threat of hazards by various types of disasters which is caused by natural processes and human activities. On the other hand, the vulnerability has increased either on physical, social-economic and cultural thus increasing the risk of disasters. After the endorsement of Law 24 Year 2008 on Disaster Relief and Government Regulation No. 21, 22, and 23 in 2008, the National Government, the Local Government and the community are requested to make efforts to disaster reduction through mitigation and ecological adaptation activities, especially in the disaster-prone area. Disaster management has undergone a fundamental change from managing the disaster to manage disaster risks. In the context of spatial planning, according to Law 26 Year 2008 on spatial planning, the integration and revision of the spatial planning required layout of the island's ecosystem-based and disaster mitigation for disaster-prone areas, in order to achieve the community coping capacity to disaster leading to safe, comfortable, productive, and sustainable living.